Analisa Pengembangan Wisata Alam dan Budaya Lokal: Studi Kasus di Kecamatan Siberut Selatan, Kepulauan Mentawai - Setiawati, Sri; Febriamansyah, Rudi; Reflinaldon, Reflinaldon; Rusfidra, Rusfidra; Lucida, Henny; Mutiara, Vonny Indah; Al Giffari, Muhammad; Zis, Sirajul Fuad; Fiza, Nora (Universitas Pendidikan Indonesia, 2025)
AbstractWest Sumatra, especially the Mentawai Islands, is a tourist destination that many foreign tourists visit, especially for marine tourism such as surfing. However, the number of archipelago tourist visits solely for traveling is still relatively low. In fact, the Mentawai Islands have the potential for natural and cultural tourism which includes interesting traditional architecture for ecotourism. This study aims to identify the potential of natural attractions, buildings, and local culture in South Siberut sub-district and analyze the tourism development design. The research used qualitative methods through in-depth interviews, focus group discussions (FGDs), field observations, and secondary data analysis. The results showed that the three villages, namely Madobag, Muntei, and Matotonan, have great potential but face challenges in the form of inadequate accessibility, attractions that have not been well managed, limited supporting facilities, and weak Pokdarwis institutions. The design of tourism development in Siberut Sub-district aims to create sustainable tourism that not only increases tourist visits, but also provides economic, social and environmental benefits for local communities AbstrakSumatera Barat, khususnya Kepulauan Mentawai, merupakan destinasi wisata yang banyak dikunjungi wisatawan mancanegara, terutama untuk wisata bahari seperti surfing, tetapi, masih rendah jumlah kunjungan wisatawan nusantara. Padahal, Kepulauan Mentawai memiliki potensi wisata alam dan budaya yang meliputi arsitektur tradisional yang menarik untuk ekowisata. Studi ini bertujuan untuk mengidentifikasi potensi objek wisata alam, bangunan, dan budaya lokal di Kecamatan Siberut Selatan serta menganalisis rancang bangun pengembangan wisatanya. Penelitian menggunakan metode kualitatif melalui wawancara mendalam, diskusi kelompok terfokus (FGD), observasi lapangan, dan analisis data sekunder. Hasil penelitian menunjukkan bahwa ketiga desa, yaitu Madobag, Muntei, dan Matotonan, memiliki potensi besar dengan sejumlah tantangan berupa aksesibilitas yang kurang memadai, atraksi yang belum dikelola dengan baik, fasilitas pendukung yang terbatas, serta kelembagaan Pokdarwis yang masih lemah. Rancang bangun pengembangan wisata di Kecamatan Siberut bertujuan untuk menciptakan pariwisata berkelanjutan yang tetapi juga memberikan manfaat ekonomi, sosial, dan lingkungan bagi masyarakat lokal.